Vacuum coated Sb2S3 thin films: Thermal treatment and the evolution of its physical properties. (June 2017) - Sotelo Marquina, R.G.; Sanchez, T.G.; Mathews, N.R.; Mathew, X.
Graphical abstract: Highlights: Post-deposition thermal processing parameters of Sb2 S3 thin films optimized. Significant change in morphology and photosensibility observed in a small temperature window. 325 °C is a critical point in thermal processing of Sb2 S3 thin films. The photosensibility improved by 200 times upon annealing at optimized condition. Abstract: In this work, we report a detailed study of the post-deposition thermal processing and material properties of Sb2 S3 thin films deposited by thermal evaporation under vacuum. The effect of the annealing temperature on the structural, morphological, optical, opto-electronic, spectroscopic, and electrical properties of the films was investigated using various tools such as XRD, AFM, UV–vis spectroscopy, Raman spectroscopy, Ellipsometry, photoconductivity, Seebeck effect, and Kelvin probe. The annealing temperature had an interesting influence on the grain growth, and morphology of the films; in a small temperature window of 10 °C, the change in grain size and shape was striking. The annealing temperature of 325 °C was identified as a critical point at which the grain size is smallest and the morphology is exceptionally homogeneous. Two highly noticeable features were the change in morphology and photosensibility. The photosensibility increased from 0.6 for the as-deposited film to 132 after annealing at 400 °C.